Design of Wideband Reflectarray and Transmitarray Antennas With Low Sidelobe and Cross-Polarization Levels Using a Multifunctional Ultrathin Metasurface - Yufang Wang; Yuehe Ge; Zhizhang Chen; Ziheng Zhou (IEEE Open Journal of Antennas and Propagation, 2024)
Ensuring a low cross-polarization level (CPL) is imperative in the design of antennas with a low sidelobe level (SLL). This paper introduces an innovative approach for designing wideband, high-gain, low-sidelobe, and low-cross-polarization reflectarray (RA) and transmitarray (TA) antennas. The methodology leverages a groundbreaking metasurface endowed with the capability for independent amplitude and phase manipulation in both transmission and reflection modes. Initial characterization robustly verifies the metasurface’s proficiency in independently controlling amplitude and phase in reflection and transmission modes. Importantly, the study demonstrates that this metasurface enables the straightforward attainment of low CPL in the design of low-SLL RA and TA antennas. The study progresses to the design, fabrication, and testing of three RA and TA antennas. The obtained simulated and measured results affirm their exceptional performance in terms of wideband, high-gain, low-SLL, and low-CPL characteristics.